Characteristics Of House Facade And Its Impact To Residents' Visual Privacy In Erbil, Iraq - Al-Botany, Hussien Salman Abdullah (2018)
This study investigates the impact of house facade characteristics on the residents’ visual privacy in Erbil City, Iraq. The aim is to examine the correlation between house facade characteristics’ factors and residents’ visual privacy. The study will propose a conceptual model, which provides certain guidelines for architects to apply in designing modern houses’ facades. This study also aims to determine the most influential factor in achieving residents’ visual privacy. The study applies quantitative and qualitative research methods to answer the research objectives. Based on the mixed-method approach, a qualitative and a quantitative survey were carried out.